PLANNING FOR HERITAGE TOURISM: THE CASE OF LANGKAWI GEOPARK - Puay Liu, Ong; Abd Halim, Sharina (PLANNING MALAYSIA, 2011)
The principal building blocks underlying Langkawi’s status as a tourist destination and a geopark are its nature and culture. Both these resources provide the platform for Langkawi to grow as a tourist destination since 1980s and receiving the geopark status by GGN and UNESCO in 2007. This paper discusses that while tourism is a commercial enterprise, it has an important role in ensuring Langkawi’s natural environment is well-protected, and local communities’ cultural traditions safeguarded. Central to this need for protection is ‘heritage’ - the basic ingredient in sustaining Langkawi as a premier tourism destination. This necessitates the need to view tourism and heritage management as interdependent, as both rely on the same ‘heritage resources’. Planning can act as the bridge to connect tourism, whose products are identified for their extrinsic values as tourist attractions, and heritage in which assets are identified for their intrinsic values to a community, state, country and the world.